Numerical investigation on the coupled mechanisms of bubble breakup in a venturi-type bubble generator. Issue 1 (31st December 2022) - Li, Qiang; Ming, Dezhi; Lei, Mao; Guo, Xu; Liu, Jialin; Zhu, Haowei; Fang, Liang; Wang, Zhenbo
Abstract : The bubble breakup mechanism in a venturi-type bubble generator is a hot research topic, and the bubble breakup mechanisms induced by the axial regional flow field characteristics has long been studied and debated. A coupled volume of fluid and large eddy simulation numerical simulation method was conducted within the OpenFOAM ® framework to track the two-phase interfaces and transient turbulence characteristics of the flow field in a venturi-type bubble generator. A turbulence inlet database was established to ensure the reliability of the numerical solution and the economy of the calculation. The results indicated that the bubble breakup induced by the axial regional flow field characteristics of the divergent section can be divided into a steady-state disturbed breakup pattern and an unsteady-state disturbed breakup pattern macroscopically, the latter playing a dominant role in generating fine bubbles. Furthermore, a series of typical bubble breakup processes were captured via a Lagrangian approach that showed that interfacial instability played an important role at each stage of bubble transport: Kelvin–Helmholtz instability caused bubbles to detach from the gas film during the steady-state disturbed breakup pattern, and Rayleigh–Taylor instability induced the deformation of detached bubbles in the unsteady-state disturbed region. Additionally, viscous shear force strengthened the interfacial instability in the binary breakup process, and turbulent fluctuations and collisions contributed to the shattering of defective bubbles. Moreover, a shearing-off process tended to occur in regions with small vorticity fluctuations, therefore playing a small role in creating large clusters of bubbles.